Novel Suturing Methods for the Management of Traumatic Choroidal Avulsion in Globe Injuries - Chen, Huijin; Yang, Jiarui; Wang, Changguan; Feng, Xuefeng; Feng, Kang; Ma, Zhizhong (Frontiers in Medicine, 2022)
Purpose: To explore the long-term efficacy of novel choroidal suturing methods including trans-scleral mattress suturing (TSS) and intraocular suturing (IOS) in treatment of choroidal avulsion. Methods: A total of 24 patients with 24 eyes who were diagnosed with choroidal avulsion were enrolled in this study. Demographic characteristics, baseline information of trauma, best corrected visual acuity (BCVA) and intraocular pressure (IOP) were collected before surgery, and the anatomic abnormities of the globe were recorded before or during the surgery. All patients were diagnosed with choroidal avulsion and underwent choroid suturing treatment during vitrectomy, postoperative functional variables including BCVA and IOP, anatomic variables including retinal and choroidal reattachment rate, silicone oil migration rate were recorded at the regular follow-ups at least 1 year after surgery. Results: All patients with open globe injury involved zone III, 70.8% patients presented with two quadrants of the avulsed choroid, and 29.2% with one quadrant involved; moreover, all patients were complicated with retinal detachment (RD), of which 58.3% of patients had closed funnel retinal detachment. TSS was applied in nineteen patients and IOS in five patients. Postoperatively, a significant improvement on LogMAR BCVA was observed at each follow-up from 3.57±0.69 before surgery to 2.82±0.98 at the last follow-up (P<0.05), and the proportion of NLP was also reduced from 69.6% to 37.5%. IOP was markedly elevated from 6.4±4.1mmHg preoperatively to 11.3±4.3mmHg at the last follow-up (P<0.05). Choroidal reattachment was achieved in 91.7% patients, two patients were observed with silicone oil migration at 3 months after surgery and underwent drainage of suprachoroidal silicone oil and sclera buckling, meanwhile, retinal attachment was observed in 95.8% patients, only one patient developed partial RD due to postoperative proliferative vitreoretinopathy, and secondary vitrectomy was performed, all patients were observed with complete retinal and choroidal attachment at the last follow-up. Eventually, four patients were silicone oil free, and 20 patients were silicone oil dependent. Conclusions: Choroidal suturing proves to be an effective method to fix the avulsed choroid, which greatly improved the BCVA and maintained the IOP, and efficiently increased the choroidal and retinal reattachment rate and preservation of the eyeball.